Formaldehyde Biosensors in Foodstuffs Applying Nano Gold Entrapped in p-HEMA Deposited on Screen-Printed Carbon Electrodes: A Short Review - Alva, S; Heng, LY; Ahmad, M; Sundari, R (Elsevier, 2024)
Indexed by WOS/SCOPUS